The teacher as leader: Effect of teaching behaviors on class community and agreement - Beth Rubin (Athabasca University Press, 2013)
This article examines the effects of teaching behaviors in online university classes, focusing on the agreement among class members. Literature on group leaders’ effects on group agreement about workplace climate is reviewed. Hypotheses are generated about the effects that teachers of online courses, as class leaders, have on both the level and agreement about the community of inquiry. They are tested with a sample of 874 students in 126 online courses. The aggregate class level and strength of agreement about the teaching presence have significant effects on the level and agreement about cognitive presence and social presence. Although the aggregate levels and agreement about community of inquiry are related, different patterns emerge.